Ontogenetic regulation of leukocyte recruitment in mouse yolk sac vessels - Sperandio, Markus; Quackenbush, Elizabeth J.; Sushkova, Natalia; Altstätter, Johannes; Nussbaum, Claudia; Schmid, Stephan; Pruenster, Monika; Kurz, Angela; Margraf, Andreas; Steppner, Alina; Schweiger, Natalie; Borsig, Lubor; et al. (Blood, 2013)
In adult mammals, leukocyte recruitment follows a well-defined cascade of adhesion events enabling leukocytes to leave the circulatory system and transmigrate into tissue. Currently, it is unclear whether leukocyte recruitment proceeds in a similar fashion during fetal development. Considering the fact that the incidence of neonatal sepsis increases dramatically with decreasing gestational age in humans, we hypothesized that leukocyte recruitment may be acquired only late during fetal ontogeny. To test this, we developed a fetal intravital microscopy model in pregnant mice and, using LysEGFP (neutrophil reporter) mice, investigated leukocyte recruitment during fetal development. We show that fetal blood neutrophils acquire the ability to roll and adhere on inflamed yolk sac vessels during late fetal development, whereas at earlier embryonic stages (before day E15), rolling and adhesion were essentially absent. Accordingly, flow chamber experiments showed that fetal EGFP+ blood cells underwent efficient adhesion only when they were harvested on or after E15. Fluorescence-activated cell sorter analysis on EGFP+ fetal blood cells revealed that surface expression of CXCR2 and less pronounced P-selectin glycoprotein ligand-1 (PSGL-1) begin to increase only late in fetal life. Taken together, our findings demonstrate that inflammation-induced leukocyte recruitment is ontogenetically regulated and enables efficient neutrophil trafficking only during late fetal life.
Prepublished online as Blood First edition paper, March 22, 2013
Gesehen am 14.02.2022